Efeitos da redução do nível da água sobre a dinâmica do zooplâncton e seus predadores em dois lagos rasos tropicais semiáridos - Medeiros, Paulo Ivo Silva de (2020)
The reduction in the volume of lakes and reservoirs due to increased water deficit during periods of drought should affect the structure and trophic dynamics of these ecosystems, increasing the density of organisms, the rates of encounter between predators and prey and, consequently, the predation pressure. The objective of this study was to investigate the effects of water level reduction caused by extreme drought events on the densities of zooplankton organisms and their predators in two reservoirs of the Brazilian semiarid tropical region. The densities of zooplankton organisms (rotifers, cladocerans and copepods) and their main predators (fish fingerlings and Chaoboridae larvae) were monitored for 24 months in two artificial shallow lakes of the Brazilian semi-arid region during a period of drought (2012-2014). In one of the lakes, about 5.8 tons of adult fish were removed to prevent massive fish mortality when the volume of water and oxygen reached a critical level. Zooplanktonic organisms were collected monthly by means of vertical trawls with a plankton net (68 µm) opening and their predators were collected monthly by means of horizontal trawls with an ichthyoplankton of 500 µm mesh size and a flow meter to measure the filtered volume. The organism densities were analyzed over the study period and Spearman correlations were performed to evaluate the possible interactions between zooplanktonic organisms and their predators and the effects of reduced water volume on the studied organisms. In both lakes, rotifers were the group with the highest density and Chaoboridae larvae were the most abundant predators. In the lake where there was no removal of adult fish, the densities of fish larvae increased, the densities of Chaoboridae larvae decreased and those of copepods increased with the reduction of the water level. On the other hand, in the lake where adult fish were removed, the densities of fish larvae and rotifers decreased while the densities of Chaoboridae larvae increased with the reduction of the water level. These results indicate that the water level reduction caused by drought tends to vary the abundance of Chaoboridae and fish larvae, changing the relative importance of predation by vertebrates and invertebrates and the structure of zooplankton communities depending on local conditions.